Nature, action, and reason : a comparative study of the Aristotelian and Nietzschean approaches to tragedy - Chen, Min Suen (Nanyang Technological University, 2020)
Tragedy is deemed the highest version of art in the Aristotelian and the Nietzschean framework. Although both sets of theories are built on the shared recognition on the foundational position of nature, they have in fact branched into distinct approaches to art in general. The disagreement on art then results in their opposition in the theory of tragedy. In this paper, I seek to examine the mechanism behind such transformation through observations from their shared starting point of nature to the point where the opposition is present in the discussions on tragedy. I would like to show that the disagreement in art ultimately lies in their distinct approaches toward rationality. Furthermore, as Nietzschean theory rejects a ‘naturalization’ attempt to explain human life, I would show that the Aristotelian approach actually matches the Nietzschean framework of ‘naturalization’, thus providing an explanation to the aforementioned transformation.